Clinical and epidemiological characterization of gunshot or stab injuries hospital central universitario Antonio Maria Pineda (Revista Venezolana de Salud Pública, 2018)
The present study aims to determine the clinical and epidemiological characteristics of gunshot injuries or stab enteringthe University Central Hospital "Antonio Maria Pineda", Barquisimeto, Lara state. A study was conducted descriptive,transversal. The population consisted of 269 injured patients admitted to the emergency room of Hospital in the periodSeptember-October 2012. The data were collected in a structured form in parts III, among the findings, we found a higherpercentage of injuries among males (94.1%) in the age group of 20 and 35 years (60.2%), in workers (53.2%) andin IV (69.1%). Sunday was the day with the highest number of injuries (23.4%), the time of day with the highestoccurrence was the night (44.6%). The 97.4% occurred in Lara state of which 64.5% were in the municipality Iribarren,being the Juan de Villegas parish which has the highest percentage of injuries (25.4%). The most common place ofoccurrence was in the street (72.9%) ̧ moreover, theft (48.7%) was the main reason for aggression, predominantly used afirearm (85.5%) mostly short (60.9%) injuries were complicated in 83.6% of cases, compromising the neurovascularsystem with 73.8% in the degree of contamination was demonstrated 39.4% of contaminated and clean-contaminated, themost affected anatomical region corresponded to multiple body regions (20.4%). This research provides data for thedevelopment of protocols for the immediate care of the gunshot or stabbed patient.
Keywords: Violence; Weapons; Lesions; Prevention